2013
DOI: 10.5586/aa.1986.012
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of more important mineral components by common field weeds on loess soils

Abstract: We have determined the contents of N, P, K, Ca, Mg, Na, Fe, Cu, Mn and Zn in winter wheat, spring barley, sugar beets and winter rape, as well as in the most common weed species infesting these crops. It was established that the percentage of mineral components in the dry matter of the majority of weeds is higher than in that of the cultivated plants. The most dangerous weed species competing with plants for the investigated nutrients were: <i>Chenopodium album, Cirsium arvense, Convolvulus arvensis, Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, weed and crop growth may be limited by nutrient availability, even when N is added at sufficient rates . Weeds can have a higher nutrient requirement than crops and compete strongly for nutrients, even when high rates of fertilizer are applied (Burgos et al 2006;Johnson 2010b, 2011c;Malicki and Berbeciowa 1986). High N application rates can also result in greater leaf area indices of weeds and thereby reduce the light available to rice (Ampong-Nyarko and De Datta 1993).…”
Section: Weed Managementmentioning
confidence: 99%
“…However, weed and crop growth may be limited by nutrient availability, even when N is added at sufficient rates . Weeds can have a higher nutrient requirement than crops and compete strongly for nutrients, even when high rates of fertilizer are applied (Burgos et al 2006;Johnson 2010b, 2011c;Malicki and Berbeciowa 1986). High N application rates can also result in greater leaf area indices of weeds and thereby reduce the light available to rice (Ampong-Nyarko and De Datta 1993).…”
Section: Weed Managementmentioning
confidence: 99%
“…Carlson and Hill (1985) observed that wild oat was able to utilize nutrients, such as nitrogen, more efficiently than wheat (Triticum aestivum L.). Teyker et al ( 1991) noticed that red root pigweed responded more to supplemental N than maize (Zea mays) and accumulated 2.5 times as much N in shoots when supplied with large amounts of N. Weeds require the same nutrients as crops and frequently are more effective in absorbing them (Malicki and Berbeciowa 1986); therefore, a competitive advantage is gained by the weed in many circumstances.…”
Section: Nitrogenmentioning
confidence: 99%